2021
DOI: 10.3389/fmicb.2021.718497
|View full text |Cite
|
Sign up to set email alerts
|

Viable Severe Acute Respiratory Syndrome Coronavirus 2 Isolates Exhibit Higher Correlation With Rapid Antigen Assays Than Subgenomic RNA or Genomic RNA

Abstract: Background: Rapid identification and effective isolation are crucial for curbing the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). To meet this requirement, antigen-detection rapid diagnostic tests (Ag-RDTs) are essential.Methods: Between February 2020 and August 2020 we performed a cohort study of patients with confirmed COVID-19. The clinical performance of Ag rapid fluorescence immunoassay (FIA) and Ag Gold was evaluated and compared in parallel with genomic and subgenomic real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…1). Indeed, most studies on Ag-RDT detection show good concordance with RT-PCR positivity when Ct values are below 25-30, a viral load compatible with the presence of infectious virus, whereas higher Ct values give less reliable results 34,[37][38][39][40][41] .…”
Section: Antigen-detecting Rapid Diagnostic Testsmentioning
confidence: 99%
“…1). Indeed, most studies on Ag-RDT detection show good concordance with RT-PCR positivity when Ct values are below 25-30, a viral load compatible with the presence of infectious virus, whereas higher Ct values give less reliable results 34,[37][38][39][40][41] .…”
Section: Antigen-detecting Rapid Diagnostic Testsmentioning
confidence: 99%
“…A study showed that antigen-based RDTs detected 100% of infection in 15 cell culture-positive samples (n = 15) and were 66.7% effective in distinguishing viable samples from those with subgenomic RNA. In addition, discordant samples with positive RT-PCR but negative RDT were actually culture negative [ 36 ]. Based on the sample, it was found that nasopharyngeal swabs were more sensitive than nasal swabs using RDT with 100% and 98.7% sensitivity, respectively [ 37 ].…”
Section: Antigen-based Strategymentioning
confidence: 99%
“…Ag-RDT positive results have been associated with the ability to culture SARS-CoV-2 in vitro or viral loads consistent with a transmissible virus. Therefore, Ag-RDTs have been used as a surrogate for SARS-CoV-2 communicability ( 5 9 ). Nova Scotia was the first Canadian province to implement Ag-RDTs for self-perceived asymptomatic individuals in low-barrier volunteer-led community testing centers, to identify individuals at high risk of transmitting SARS-CoV-2 that might otherwise have gone unnoticed ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%